The Role of Knowledge, Self-Efficacy, and Social Support in Self-Care Behaviors among Diabetic Patients: A Meta-Analysis - Ayu Nanda Sari; Diyah Nawangwulan (Masters Program in Public Health, Sebelas Maret University, 2021)
Background: Diabetes mellitus is recognized as one of the emerging public health problems globally, in which the number of cases and prevalence have been steadily increasing over the past few decades. To reduce the burden posed to health systems and afflicted individuals, patients need to adopt self-care practices. At the same time, some studies found knowledge, self-efficacy, and support were essential. Hence, this meta-analysis aimed to assess these predictors of self-care behaviors among diabetic patients.Subjects and Method: This meta-analysis followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. We conducted a systematic search in electronic databases for observational studies about knowledge, self-efficacy, and family or social support for diabetic self-care behaviors published between 2012 and 2022. The Joanna Briggs Institute’s Critical Appraisal tool was used. For statistical analysis such as I-squared and Begg and Egger’s tests, the Review Manager (RevMan) 5.3 software was employed. Tables and forest plots were presented with 95% confidence intervals (CI). Statistical significance was declared at a p-value < 0.05.Results: Twelve studies with 5,482 participants were included. Good self-care behaviors were significantly associated with adequate diabetic knowledge (AOR= 2.22; 95% CI= 1.24 to 3.98; p= 0.007) and having family or social support (AOR= 2.5; 95% CI= 1.98 to 3.16; p<0.001), whereas poor self-efficacy was a significant predictor of poor self-care behaviors (AOR= 2.46; 95% CI= 1.66 to 3.65; p<0.001).Conclusion: Diabetic knowledge, self-efficacy, and family or social support are essential correlates and predictors of self-care behaviors. Researchers, healthcare professionals, third-sector organizations, and policymakers can use these findings to re-evaluate.Keywords: diabetes, self-care behaviors, knowledge, self-efficacy, social support, meta-analysisCorrespondence:Ayu Nanda Sari. Faculty of Medicine, Universitas Malikussaleh. Jl. H. Meunasah Uteunkot Cunda, Lhokseumawe 24351, Aceh, Indonesia. Email: ayunandasari@student.uns.ac.id. Mobile: +6285210688872. Journal of Health Promotion and Behavior (2021), 06(03): 250-262DOI: https://doi.org/10.26911/thejhpb.2021.06.03.08